Recipe composition and functional orientation of a specialized product for metabolism disorders correction in inflammatory diseases - E. Y. Lobach; V. M. Poznyakovsky; A. N. Austrievskikh (Новые технологии)
Characteristics of initial raw material and its active components, which allowed to scientifically substantiate qualitative and quantitative composition of the formulation of a new phytocomplex in the form of dietary supplements have been considered. Synergistic properties of prescription components allowed to determine the functional orientation of the developed product - as a processing aid in prevention and complex treatment of acute inflammatory diseases, which was confirmed by clinical trials in a group of patients with focal pneumonia and acute respiratory viral infection. A specialized product is included in the federal register of dietary supplements, approved and introduced into production at the enterprises of the Artlife company (Tomsk).